2011
DOI: 10.1128/mcb.05207-11
|View full text |Cite
|
Sign up to set email alerts
|

The parkin Mutant Phenotype in the Fly Is Largely Rescued by Metal-Responsive Transcription Factor (MTF-1)

Abstract: The gene for Parkin, an E3 ubiquitin ligase, is mutated in some familial forms of Parkinson's disease, a severe neurodegenerative disorder. A homozygous mutant of the Drosophila ortholog of human parkin is viable but results in severe motoric impairment including an inability to fly, female and male sterility, and a decreased life span. We show here that a double mutant of the genes for Parkin and the metal-responsive transcription factor 1 (MTF-1) is not viable. MTF-1, which is conserved from insects to mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 75 publications
4
35
1
Order By: Relevance
“…In line with the findings presented here, elevated expression of MTF-1 dramatically improved the condition of the parkin mutant (Saini et al, 2011). However, unlike the Ab transgenics described here where extra zinc was at least as bad, if not worse than copper, zinc supplementation had a strong beneficial effect on the parkin mutant .…”
Section: Figuresupporting
confidence: 76%
“…In line with the findings presented here, elevated expression of MTF-1 dramatically improved the condition of the parkin mutant (Saini et al, 2011). However, unlike the Ab transgenics described here where extra zinc was at least as bad, if not worse than copper, zinc supplementation had a strong beneficial effect on the parkin mutant .…”
Section: Figuresupporting
confidence: 76%
“…As previously reported, MTF1 binds specifically to heavy metal-responsive DNA sequence elements in the enhancer/promoter region of metallothionein (MT) genes to regulate their expression (26,27). MT genes, such as MT1X and MT2A, encode small cysteine-rich proteins that scavenge heavy metals, such as Zn (II), Cd (II) and Cu (I), and reactive oxygen species (28,29). Arriaga et al (30) found that the expression of 5 isoforms of MTs, consisting of MT1G, MT1E, MT1F, MT1H and MT1M, were lost during the transition between normal colorectal mucosa and CRC, and the expression of MTs was associated with a shorter survival time in CRC patients (30).…”
Section: Discussionmentioning
confidence: 97%
“…Previous in vitro evidence has shown that parkin can modulate levels of the 1B isoform of DMT1 through ubiquitination 32 . Moreover, Drosophila studies show that both pharmacological (BCS/BPD) or genetic (increased expression of the metal responsive transcription factor 1, MTF-1) chelation of redox-active metals decreases oxidative stress, improves reduced lifespan and normalizes metal concentrations in parkin mutant flies 33, 34 . Therefore, parkin’s regulation of metal homeostasis and its role as an E3 ligase raise the possibility of parkin-mediated regulation of Mn-responsive proteins.…”
Section: Discussionmentioning
confidence: 99%